Challenges in diagnosis of spinal epidural abscess: A case report - Yang, Xiaowei (Medicine (Baltimore), 2019)
RATIONALE: Spinal epidural abscess (SEA) is a rare condition that shows a high prevalence in immunocompromised patients. The clinical presentation of SEA includes the “classic triad” of pain, fever, and neurological dysfunction. However, these nonspecific features can lead to a high rate of misdiagnosis. SEA may lead to paralysis or even death; thus, prognosis of these patients remains unfavorable. PATIENT CONCERNS: We report a case of a multilevel (T6–T12) SEA in a 22-year-old woman. DIAGNOSIS: The patient was initially diagnosed with spinal tuberculosis at a local hospital based on a history of tuberculosis exposure, as well as radiography and computed tomography. Histopathological examination of the tissue resected during laminectomy confirmed the diagnosis of SEA in this patient. INTERVENTIONS: The patient underwent multilevel laminectomy combined with long-term antibiotic therapy. OUTCOMES: Physical examination performed 16 months postoperatively revealed that superficial and deep sensation was restored to normal levels in the lower extremities with improvement in the patient's motor function (muscle strength 2/5). LESSONS: This case report indicates that whole spine magnetic resonance imaging is warranted in patients with SEA and that prompt surgical intervention is important at symptom onset. Long-term antibiotic therapy is also essential postoperatively.